Industrial training report: MH Milk Sdn Bhd / Ammar Sakhawi Azman - Azman, Ammar Sakhawi (Universiti Teknologi MARA, Perlis, 2023)
This report highlights my 24-week marketing internship experience with Mh Milk SDN BHD (Farm Fresh Penang). The company is one of the Farm Fresh brand'sstockists and serves as the primary warehouse and distributor for Farm Fresh goods inPenang. I worked as an intern for 24 weeks, starting on March 1st,22023, and finishing onAugust 15th,2023. I had the chance to discover more about the business' operations andthe marketing of dairy products. I had learned a lot from the trainings, meetings,conversations, events, and dealing with clients from various backgrounds under thedirection of the marketing team. This training report is closely related to the sales and marketing of Farm FreshPenang and not only contains my personal reflections during the internship but alsodiscusses the SWOT analysis and recommendations that have been made throughout theinternship training. The SWOT analysisprovided valuable insights into the strengths,weaknesses, opportunities, and threats of Farm Fresh Penang's sales and marketingstrategies. Based on these findings, several recommendations were made to enhance thecompany's competitive advantage and market position. These recommendations focused onareas such as expanding distribution channels, improving product packaging, and branding,and implementing targeted advertising campaigns to reach a wider consumer base.Overall, this training report serves as a comprehensive overview of my internship experienceand offers actionable suggestions. This report also sums up the opportunities for myexperience and learning in this company. All these factors help me be more knowledgeableand professional in the field of marketing.